Pengaruh Online Customer Review, Online Customer Rating Dan Kepercayaan Terhadap Keputusan Pembelian Online (Studi Kasus Pada Mahasiswa Feb Universitas Pgri Semarang) - Anna Irma Rahmawati (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2022)
This study aims to determine the effect of online customer reviews, online customer ratings, and trust on online purchasing decisions at Shopee. The type of research used is quantitative with non-probability sampling method and a sample of 90 respondents who are FEB students at PGRI University Semarang who have used Shopee. Data analysis in this study is using Multiple Linear Regression. The results show that online customer reviews and online customer ratings have no effect on online purchasing decisions, and trust affects online purchasing decisions at Shopee.